Dimensions of Participation in Simon's Design. - Carroll, John M. (Design Issues)
The article discusses the concept of participatory design through a discussion of the book, The Sciences of the Artificial, by Herbert Simon. Participatory design is a high-level feature of design methods that can be implemented in a myriad of ways. It contains the following dimensions: domains of human activity, roles of stakeholders in a design, types of shared design representations, the scope and duration of participatory interactions, and the relationship of users to design activity with respect to changes in their knowledge and skill. In the book, Simon characterizes design as central to what humans are and what they do.